Germanic heritage languages in North America : acquisition, attrition and change - Johannessen, Janne Bondi; Salmons, Joe, 1956- (Studies in language variation, 2015)
This book presents new empirical findings about Germanic heritage varieties spoken in North America: Dutch, German, Pennsylvania Dutch, Icelandic, Norwegian, Swedish, West Frisian and Yiddish, and varieties of English spoken both by heritage speakers and in communities after language shift. The volume focuses on three critical issues underlying the notion of 'heritage language': acquisition, attrition and change. The book offers theoretically-informed discussions of heritage language processes across phonetics and phonology, morphology, syntax and semantics and the lexicon, in addition to work on sociolinguistics, historical linguistics and contact settings. With this, the volume also includes a variety of frameworks and approaches, synchronic and diachronic. Most European Germanic languages share some central linguistic features, such as V2, gender and agreement in the nominal system, and verb inflection. As minority language faced with a majority language like English, similarities and differences emerge in patterns of variation and change in these heritage languages. These empirical findings shed new light on mechanisms and processes --